DEVELOPMENT OF E–BOOK BASED FLIPBOOK OF RECOUNT TEXT MATERIAL TO IMPROVE STUDENTS READING SKILL - Hadi, Aisyah; Niah, Siti (Jurnal Basataka (JBT), 2025)
Motivation and reading skills are important aspects that must be considered by educators, especially in learning English. One effort to improve the reading skills of grade XI students of State Vocational High School 7 Pekanbaru is through the development of flipbook-based e-books that focus on recount texts. This study aims to evaluate the effectiveness of using flipbook-based e-books in improving students' motivation and reading skills. The subjects of the study consisted of 30 grade XI students of State Vocational High School 7 Pekanbaru in the 2024/2025 academic year. Data collection used a motivation questionnaire and pretest and posttest to measure the improvement in reading skills. The method used is Research and Development (R&D) with the application of the ADDIE model consisting of several stages, while data analysis uses the N-Gain value and the percentage of student responses. The results of the study showed a significant increase with an average N-Gain value of 0.8509 which is included in the "high" category and the percentage of positive student responses reaching 84.13%. Based on these findings, it can be concluded that the use of flipbook-based electronic books has proven effective in increasing the motivation and reading skills of class XI students at State Vocational High School 7 Pekanbaru.